Peningkatan Kinerja Pengelola Objek Wisata Berbasis Etos Kerja Dan Digitalisasi Sistem Informasi Manajemen - Iskandar Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research is motivated by the suboptimal work ethic in Riau tourist attractions. The study was conducted at tourist attractions in Riau Province. The purpose of this study was to analyze and examine, descriptively and verifiably, the influence of work ethic on the implementation of management information systems. The research method used was quantitative, with descriptive and verifiable methods. The sampling technique used was Proportional Cluster Random Sampling. The data analysis technique used was SPSS analysis. The descriptive results of the study indicate that work ethic influences the implementation of management information systems, ranging from fair to good. The results of the verifiable study indicate that work ethic makes a significant contribution to the implementation of management information systems among tourist attraction managers. The results of the verifiable study indicate that the implementation of management information systems makes a very significant contribution to the performance of tourist attraction managers in Riau Province.